(untitled) (Bangladesh Journal of Botany, 2011)
Phosphorus deficiency caused a decrease in the accumulation of reducing sugar in the leaves and stems but increased in the roots of lentil (Lens culinaris Medik.). Accumulation of insoluble protein was depressed in lentil following P-deficiency. Phosphorus deficiency increased proline and phenolic compounds in roots and stems and anthocyanin in leaves compared to control. Key words: Phosphorus deficiency; Accumulation; Biochemical compounds DOI: http://dx.doi.org/10.3329/bjb.v40i1.7992 Bangladesh J. Bot. 40(1): 23-27, 2011 (June)